The role of social workers in promoting environmental justice for sustainable communitiesc: from an NGO perspective in the city of Tshwane - Lombard, A. (Antoinette) (University of Pretoria, 2021)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2020.